Contingent identity, rigid designation, and counterpart theory - Ramachandran, Murali (My University, 2020)
This thesis is concerned with the coherence or otherwise of contingent identity: the possibility of certain objects being identical, but not necessarily identical. The overwhelmingly dominant view, at least since Saul Kripke’s influential book, Naming and Necessity, is that the idea of contingent identity is simply incoherent. In that book Kripke puts forward compelling—many think conclusive—considerations in support of the view that any (genuine) identity statement must be necessarily true if true at all. Chapter 1 introduces Kripke’s key notion of rigid designation, which is explicated in part by distinguishing the ways names and (definite) descriptions refer, and the attendant case for his famous Necessity of Identity thesis. A key notion which emerges in elaborating rigidity is that of invoking; important differences between invoking and (rigidly) designating will emerge in later chapters. Kripke’s Necessity of Identity thesis is meant to encompass identity statements involving kinds, not just individuals—e.g. statements such as “water is H2O”, “gold is the element with atomic number 79”, “light is a stream of photons”, and “lightning is an electrical discharge”. But this dissertation will focus on the issue of whether the thesis is correct, or, at any rate, obligatory, as far as identity statements involving individuals (particular objects, entities) are concerned. My aim in this dissertation is to show that it is not. I am going to argue that while Kripke’s considerations are forceful against the most prominent conception of contingent identity, contingent self-identity as I call it, there is a different conception of contingent identity, one which piggy-backs on the possibility of contingent distinctness, that survives. But that is merely to say that there is a variety of contingent identity that is consistent with Kripke’s considerations; this is not yet motivation for endorsing such contingent identity, for holding that there are such identities. Two attempts to defend contingent identity are considered: Gallois (Chapter 2) attempts to accommodate contingent identity across worlds and contingent identity over time (occasional identity)by ‘restricting’ Kripke’s notion of rigidity in various ways, while Chandler (Chapter 3) defends it in the course of an attack on Kripke’s famous thesis that names are rigid designators. I argue that neither are successful as far their stated aims go; but Chandler’s case highlights a crucial component for defending contingent identity (distinctness): the mixed designation view, as I call it. This holds that a rigid designator of an object x may on occasion non-rigidly designate a possibly distinct object y. I try and make sense of this by way of considering what I call tethered designators, which involve an invoking expression but which may designate an object that is distinct from the invoked one. This leads to the introduction of the notion of a counterpart of an object, and the basic idea behind counterpart theory: that modal facts about an object  may be made true by non-modal facts about another object, (is in that sense a counterpart of ).Chapter 4then introduces David Lewis’s original counterpart theory, which is motivated by his modal realism, and two alternative approaches from Graeme Forbes and Murali Ramachandran—(I allude to myself in the third-person when discussing published material)—respectively. Their various takes on contingent identity and related issues are explored. Counterintuitive results arising from allowing an object to have more than one counterpart at a world appear inevitable. A marriage of Forbes’ approach and Ramachandran’s is floated at the end of the chapter that minimizes counterintuitive results. Chapter 5begins by noting that a convincing case for contingent identity across worlds is still wanting. It provides one by way of considering Chisholm’s modal paradox; objections to the Chandler–Salmon strategy of rejecting the S4-axiom [→] are pursued; I argue that this strategy does not address variations of the paradox, and that a proper solution needs to endorse contingent identity and to look to counterpart theory for a suitable logic. However, only a many-one counterpart theory—i.e. one which allows many objects at one world to have a common counterpart at another, but disallows an object having more than one counterpart at any world—iscalled for. I propose a development of the Forbes-Ramachandran (FR-) approach arrived at the close of Chapter 4 which incorporates many-one counterpart models. My proposal removes the remaining counterintuitive results from the FR-approach. In the final sections of the chapter I give (very) brief motivations for endorsing occasional identity and what I call sortal-relative contingent identity, and go on to suggest how the FR-approach, enriched with many-one counterpart models, might be modified so as to accommodate them
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020